Hubungan Konformitas Teman Sebaya dengan Perilaku Seksual Pranikah Pada Remaja di SMA Negeri 1 Ngemplak - Yuliana, Yeni; Dwi Yati (Jurnal Indonesia Sehat, 2023)
Background: Conformity is an activity of imitating someone's actions that are positive or negative to change behavior and affect the beliefs of others so that they do the same thing. The desire for conformity can cause adolescents to engage in deviant behavior such as premarital sexual behavior. Objective: This research aims to find out the correlation between peer conformity and premarital sexual behavior in adolescents at SMA Negeri 1 Ngemplak. Methodology: This research employed a quantitative method with a descriptive-analytic design using a cross-sectional approach. The population in this research was 285 students of class X and XI while the sample was 57 respondents selected using a proportionate stratified sampling. This research was conducted at SMA Negeri 1 Ngemplak, Sleman in April 2023. The measuring tools used were the peer conformity questionnaire and the premarital sexual behavior questionnaire. The bivariate data processing was done using the Spearman rho test. Results: The analysis results show that 49.1% of peer conformity that mostly occurs are in the high category while 94.7% of premarital sexual behavior in adolescents is included in the not at-risk category. The analysis of the Spearman rho test of peer conformity with premarital sexual behavior in adolescents shows a value of p = 0.001 (p <0.05) and a correlation coefficient of 0.436. There is a significant correlation between peer conformity and premarital sexual behavior in adolescents at SMA Negeri 1 Ngemplak. Conclusion: There is a correlation between peer conformity and premarital sexual behavior in adolescents at SMA Negeri 1 Ngemplak.